Citizen-scholar : essays in honor of Walter Edgar - Brinkmeyer, Robert H.; Edgar, Walter B., 1943- (The University of South Carolina Press, 2016)
"Citizen-Scholar comprises essays written in honor of Walter Edgar, South Carolina's preeminent historian and founding director of the University of South Carolina (USC) Institute for Southern Studies. In the opening overview of Edgar's impressive academic career, editor Robert H. Brinkmeyer, Jr., discusses Edgar's role as the Palmetto State's omnipresent public historian, radio program host, author of the landmark South Carolina: A History, and editor of The South Carolina Encyclopedia. The former George Washington Distinguished Professor of History, Claude Henry Neuffer Chair of Southern Studies, and Louise Fry Scudder Professor, Edgar has been recognized with inductions into the South Carolina Hall of Fame and the South Carolina Higher Education Hall of Fame and has received the South Carolina Order of the Palmetto and the South Carolina Governor's Award in the Humanities. The first section of Citizen-Scholar features personal essays about Edgar and his legacy from author and historian Winston Groom, USC vice president Mary Anne Fitzpatrick, USC president Harris Pastides, and historian Mark M. Smith. The essays that follow are written by some of the nation's most renowned scholars of southern history and culture including Charles Joyner, Andrew H. Meyers, Barbara L. Bellows, John M. Sherrer III, Orville Vernon Burton, Bernard E. Powers Jr., Peter A. Coclanis, John McCardell, James C. Cobb, Amy Thompson McCandless, and Lacy K. Ford, Jr. The second section of the collection includes essays spanning a range of regional, national, and international topics, all associated with Edgar's research. These essays were written as a tribute to Edgar, both as a historian and as a public scholar, a man actively involved in his profession as well as in his community, both locally and statewide"--